MEMODELKAN PENYALURAN KREDIT DENGAN REGRESI LINIER BERGANDA - PRADNYANI, NI WAYAN ASRI; SRINADI, I GUSTI AYU MADE; WIDANA, I NYOMAN (E-Jurnal Matematika; Vol 11 No 1 (2022)DO - 10.24843/MTK.2022.v11.i01.p354, 2022)
Credit is one of the movements carried out in economic growth.  This study aims to determine the effect of third party funds, return on assets, interest rates and inflation on lending.  The research was conducted at the Bedha Village Credit Institution (LPD) in the 1993-2020 period.  The data used is quantitative data.  The data analysis technique used is multiple linear regression with the ordinary least square (OLS) method.  The results of the study are that third party funds have a positive effect on credit loans, while interest rates have a negative effect on credit loans , return on assets and inflation have no significant effect on credit loans.